Rural Development in the 21st Century: Some Issues (The Pakistan Development Review, 1999)
Rural development is essentially a part of the process of structural transformation characterised by diversification of the economy away from agriculture. This process is facilitated by rapid agricultural growth, at least initially, but leads ultimately to significant decline in the share of agriculture to total employment and output and in the proportion of the rural population to total population [Johnston (1970)]. Rural development, as such, is not an end in itself but a means to an end and can provide the basis for a sustained and equitable economic growth of all sectors of the economy. The main theme of the paper is to contribute to the perception of rural development in Pakistan by delineating the pros. and cons. of past rural development efforts and the ensuing crisis in agriculture. Possible strategies for sustainable agricultural growth and rural development and the formal approach for their implementation are described in subsequent sections. It is argued that the whole scenario requires courage and political will of politicians to decentralise the development process. Concluding comments and future options for research appear at the end.